Abnormal coronary vasoreactivity in transient left ventricular apical ballooning (tako-tsubo) syndrome. (1st January 2018) - Verna, Edoardo; Provasoli, Stefano; Ghiringhelli, Sergio; Morandi, Fabrizio; Salerno-Uriarte, Jorge
Abstract: Background: The exact etiology and pathophysiologic mechanisms of tako-tsubo syndrome (TTS) remain controversial. Objective: To further evaluate the abnormal coronary vasoreactivity and its possible anatomical substrate in TTS. Methods: We studied 47 patients (46 women; age 67 ± 12 years) who underwent diagnostic cardiac catheterization and evaluation of coronary vasoreactivity by sequential acetylcholine (Ach), nitroglycerine and adenosine testing with angiographic and intracoronary pressure-Doppler flow monitoring. Coronary artery wall morphology was also evaluated by intravascular ultrasound (IVUS) imaging in 45 vessels of 43 patients. Results: Abnormal coronary vasoconstriction to Ach stimulation was elicited in 40 patients (85%) involving the LAD artery and its branches in 39 (83%). Abnormal microvascular function was seen in 39 (83%) patients. Overall, hyperemic microvascular resistance index (HMR) was higher and Doppler coronary flow velocity reserve (CFVR) was lower in the LAD artery territory as compared to the reference territories (2.64 ± 1.23 vs 2.05 ± 0.56; p = 0.008 and 1.95 ± 0.7 vs 2.3 ± 0.6; p = 0.018, respectively). IVUS revealed no plaque rupture, dissection or thrombosis but occult plaque formation and myocardial bridging were found as a possible anatomical substrate of endothelial dysfunction in 67% and 48.8% patients respectively. Conclusions: A global failure of coronary vasomotor function was demonstrated in most TTS patients. These findings implicate abnormal vasoconstrictive response to the activation of the sympathetic system as a potential mechanism involved in the pathogenesis of myocardial stunning in TTS. Perspectives: Competency in medical knowledge : Abnormal coronary vasoconstriction secondary to endothelial dysfunction may actively contribute to the clinical manifestation of acute coronary syndromes in patients with non-obstructive coronary disease. Translational outlook 1 : TTS patients reveal a global failure of vasomotor function with both vasoconstrictive response to acetylcholine and increased hyperemic microvascular resistances in the territory of myocardial stunning. They may also show occult coronary atherosclerosis and myocardial bridging as the anatomic substrates of endothelial dysfunction. Translational outlook 2 : The cardiac phenotype of TTS includes a high prevalence of coronary vasomotor disturbances. These findings implicate abnormal vasoconstrictive response to the activation of the sympathetic system as a potential mechanism involved in the pathogenesis of TTS in post-menopausal women. Thus, a systematic evaluation of coronary vasoreactivity could better characterize the syndrome. Graphical abstract: Diagrammatic illustration of the normal adaptation of coronary blood flow in response to sympathetic and neuro-humoral activation (A) and of the consequences of impaired flow-mediated coronary vasodilation under catecholamine overflow in the presence of coronary artery diseases and other conditions (see text).